Estetica e Biodiversità. Esperienza estetica, cura e relazione per ripensare il futuro della Biodiversità (Itinera, 2025)
Aesthetics and Biodiversity. Aesthetic experience, care and relationships to rethink the future of BiodiversityEditorial